Increased Sensitivity of Computed Tomography Scan for Neoplastic Tissues Using the Extracellular Vesicle Formulation of the Contrast Agent Iohexol - Simona Vincenti; Alessandro Villa; Daniela Crescenti; Elisabetta Crippa; Electra Brunialti; Fereshteh Shojaei-Ghahrizjani; Nicoletta Rizzi; Monica Rebecchi; Michele Dei Cas; Angelo Del Sole; Rita Paroni; Vincenzo Mazzaferro; et al. (MDPI AG, 2022)
Computed tomography (CT) is a diagnostic medical imaging modality commonly used to detect disease and injury. Contrast agents containing iodine, such as iohexol, are frequently used in CT examinations to more clearly differentiate anatomic structures and to detect and characterize abnormalities, including tumors. However, these contrast agents do not have a specific tropism for cancer cells, so the ability to detect tumors is severely limited by the degree of vascularization of the tumor itself. Identifying delivery systems allowing enrichment of contrast agents at the tumor site would increase the sensitivity of detection of tumors and metastases, potentially in organs that are normally inaccessible to contrast agents, such as the CNS. Recent work from our laboratory has identified cancer patient-derived extracellular vesicles (PDEVs) as effective delivery vehicles for targeting diagnostic drugs to patients' tumors. Based on this premise, we explored the possibility of introducing iohexol into PDEVs for targeted delivery to neoplastic tissue. Here, we provide preclinical proof-of-principle for the tumor-targeting ability of iohexol-loaded PDEVs, which resulted in an impressive accumulation of the contrast agent selectively into the neoplastic tissue, significantly improving the ability of the contrast agent to delineate tumor boundaries.